2015
DOI: 10.1063/1.4918721
|View full text |Cite
|
Sign up to set email alerts
|

Hot probe measurements of n-type conduction in Sb-doped ZnO microwires

Abstract: The charge carriers type in antimony-doped ZnO (ZnO:Sb) microwires was studied using the hot probe technique. The wires were grown by a simple thermal evaporation method. Contrary to the expected p-type behavior reported for Sb doped ZnO thin films and nanowires, our hot probe measurements of representative single Sb-doped ZnO wires show a stable n-type behavior. The hot probe technique is a simple and efficient way to determine the charge carrier type from thermoelectric measurements on a single semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Yet, the core-shell structure was not observed in these wires [42]. Another previous study found these ZnO:Sb wires to have n-type conduction [43]. Figure 1b is a representative cross-sectional SEM image of a micro-wire, which shows that the ZnO:Sb wires are composed of a core-shell heterojunction.…”
Section: Resultsmentioning
confidence: 83%
“…Yet, the core-shell structure was not observed in these wires [42]. Another previous study found these ZnO:Sb wires to have n-type conduction [43]. Figure 1b is a representative cross-sectional SEM image of a micro-wire, which shows that the ZnO:Sb wires are composed of a core-shell heterojunction.…”
Section: Resultsmentioning
confidence: 83%
“…Zinc oxide, ZnO, is a wide-bandgap semiconductor of class A 2 B 6 with a direct bandgap of width ≈3.4 eV [ 9 ]. To increase the conductivity of ZnO thin films, doping with various material, such as Al, Sn, and other, was used [ 2 , 10 ]. Al-doped ZnO (AZO) is the most widespread transparent conductive coating (TCO) based on the ZnO.…”
Section: Introductionmentioning
confidence: 99%